Review and analysis of current responses to COVID-19 in Indonesia: Period of January to March 2020 - Djalante, Riyanti; Lassa, Jonatan; Setiamarga, Davin; Sudjatma, Aruminingsih; Indrawan, Mochamad; Haryanto, Budi; Mahfud, Choirul; Sinapoy, Muhammad Sabaruddin; Djalante, Susanti; Rafliana, Irina; Gunawan, Lalu Adi; Surtiari, Gusti Ayu Ketut; et al. (Progress in disaster science, 2020)
The world is under pressure from the novel COVID-19 pandemic. Indonesia is the fourth most populous country in the world and predicted to be affected significantly over a longer time period. Our paper aims to provide detailed reporting and analyses of the present rapid responses to COVID-19, between January and March 2020, in Indonesia. We particularly highlight responses taken by the governments, non-government organisations and the community. We outline gaps and limitations in the responses, based on our rapid analysis of media contents, from government speeches and reports, social and mass media platforms. We present five recommendations toward more rapid, effective, and comprehensive responses.